Biodiversity improves the ecological design of sustainable biofuel systems. Issue 10 (17th June 2018) - Godwin, Casey M.; Lashaway, Aubrey R.; Hietala, David C.; Savage, Phillip E.; Cardinale, Bradley J.
Abstract: For algal biofuels to become a commercially viable and sustainable means of decreasing greenhouse gas emissions, growers are going to need to design feedstocks that achieve at least three characteristics simultaneously as follows: attain high yields; produce high quality biomass; and remain stable through time. These three qualities have proven difficult to achieve simultaneously under the ideal conditions of the laboratory, much less under field conditions (e.g., outdoor culture ponds) where feedstocks are exposed to highly variable conditions and the crop is vulnerable to invasive species, disease, and grazers. Here, we show that principles from ecology can be used to improve the design of feedstocks and to optimize their potential for "multifunctionality." We performed a replicated experiment to test these predictions under outdoor conditions. Using 80 ponds of 1, 100 L each, we tested the hypotheses that polycultures would outperform monocultures in terms of the following functions: biomass production, yield of biocrude from biomass, temporal stability, resisting population crashes, and resisting invasions by unwanted species. Overall, species richness improved stability, biocrude yield, and resistance to invasion. While this suggests that polycultures could outperform monocultures on average, invasion resistance was the only function where polycultures outperformed the best single species in the experiment. Due to tradeoffs among different functions that we measured, no species or polyculture was able to maximize all functions simultaneously. However, diversity did enhance the potential for multifunctionality—the most diverse polyculture performed more functions at higher levels than could any of the monocultures. These results are a key finding for ecological design of sustainable biofuel systems because they show that while a monoculture may be the optimal choice for maximizing short‐term biomass production, polycultures can offer a more stable crop of the desired species over longer periods of time. Abstract : We tested the hypothesis that multi‐species polycultures of algae can be designed to improve performance in biofuel cultivation and outperform the best single species. Our experiment of 80 open ponds (1, 100 L each) showed that polycultures can simultaneously improve crop stability, bio‐crude yield, and resistance to invasive algae ‐ three characteristics that have been difficult to attain under field conditions yet are essential for biofuels to become part of the renewable energy portfolio.